LEGO-based Robotics in Higher Education: 15 Years of Student Creativity. (26th February 2014) - Danahy, Ethan; Wang, Eric; Brockman, Jay; Carberry, Adam; Shapiro, Ben; Rogers, Chris B.
Our goal in this article is to reflect on the role LEGO robotics has played in college engineering education over the last 15 years, starting with the introduction of the RCX in 1998 and ending with the introduction of the EV3 in 2013. By combining a modular computer programming language with a modular building platform, LEGO Education has allowed students (of all ages) to become active leaders in their own education as they build everything from animals for a robotic zoo to robots that play children's games. Most importantly, it allows all students to develop different solutions to the same problem to provide a learning community. We look first at how the recent developments in the learning sciences can help in promoting student learning in robotics. We then share four case studies of successful college-level implementations that build on these developments.